Morphological and molecular identification of filamentous microorganisms associated with bulking and foaming activated sludge - Cloete, T.E. (Thomas Eugene), 1958- (University of Pretoria, 2013)
Dissertation (MSc (Microbiology))--University of Pretoria, 2005.